Anchoring Ce-modified Ni(OH)2 nanoparticles on Ni-MOF nanosheets to enhances the oxygen evolution performance. Issue 34 (12th August 2022) - Liu, Dongying; Zhao, Zhifeng; Xu, Zhikun; Li, Lin; Lin, Shuangyan
Abstract : A self-supporting electrode of Ce-m-Ni(OH)2 @Ni-MOF has been prepared by anchoring Ce-modified Ni(OH)2 nanoparticles on Ni-MOF nanosheets, and it exhibits enhanced OER performance. Abstract : Constructing a heterostructure is an efficient strategy to enhance the catalytic activity toward the oxygen evolution reaction (OER). Herein, Ce-modified Ni(OH)2 nanoparticles are anchored on Ni-MOF nanosheets by the electrodeposition strategy, forming a self-supporting electrode of Ce-m-Ni(OH)2 @Ni-MOF. The Raman spectrum proves that both Ce(OH)3 and Ce doping exist in Ce-modified Ni(OH)2 nanoparticles. The heterostructure possesses an open nanosheet structure, with a good interaction between Ni-MOF and Ce-m-Ni(OH)2, which enables efficient mass/charge transfer and the synergetic effect between Ni and Ce, leading to a high-performance electrocatalyst. Specifically, Ce-m-Ni(OH)2 @Ni-MOF achieves current densities of 50 and 100 mA cm −2 at low overpotentials of 219 and 272 mV, respectively, and retains high activity for at least 30 h.